Miliar tuberculosis with heart commitment in the immediate puerperium: a case presentation. - Geovedy Martínez García; Yoel Alberto Fleites Alonso; Nadia Sánchez Torres (ECIMED, 2011)
The miliar tuberculosis is a form of progressive illness, resultant of the dissemination of theMycobacterium tuberculosis. It affects children, old men and immune deppressed patients.The pregnancy and puerperium are two states that increase the risk of contracting thisillness. The case of a patient that begins with dyspnea, pulmonary rales and oedemas ininferior members to the 20 days of a caesarean operation, is presented. In the thorax Rx itwas detected cardiomegaly and multinodulars lung images. The echocardiogram showedsevere pericardial effusion, with fibrin remains in its interior, without signs of cardiac tamponade. Antituberculosis and heart failure treatments were administered. The clinicalevolution was favourable.The form of presentation of this illness and their similarity with other causes of heart failureunderlines the necessity of their early diagnosis, fundamentally in the countries with highdegree of infection.